Analisis Praanggapan dalam Novel yang Telah Lama Pergi Karya Tere Liye - Berliana, Dwi; Harahap, Eddy Pahar; Yusra, Hilman (Jurnal Ilmiah Dikdaya, 2024)
Pragmatics as a branch of science has another part called presuppositions. Presupposition is a part of pragmatics that talks about an event before utterances are made in communication. Good communication occurs when both parties understand each other's assumptions that they are discussing. Communication can not only occur verbally, but also in writing, one of which is writing in the form of a novel. This is the background for the researcher to choose the title Analysis of Presuppositions in the Yang Telah Lama Pergi Novel by Tere Liye. The problem in this research is how the presuppositions in the novel Yang Telah Lama Pergi by Tere Liye are. This research aims to describe the presuppositions in the novel Yang Telah Lama Pergi by Tere Liye. The approach used in this research is a qualitative approach with content analysis methods. The data collection techniques used in this research are reading techniques and note-taking techniques. The results of this research show that there are 106 narratives and dialogues that contain presuppositions. The 106 narratives and dialogues were then grouped based on the types of presuppositions according to Yule. It was found that 28 presuppositions were classified as existential presuppositions, 24 lexical presuppositions, 26 structural presuppositions, 21 factive presuppositions, 4 non-factive presuppositions, and 3 counterfactual presuppositions. The presupposition that is most often found is the existential presupposition because it uses novels as study objects which contain many narratives about the existence and state of things